Dynamic impedance measurement for condition monitoring - Chia, Jun Jie (2019)
The three main modes of public transportation in Singapore are the Mass Rapid Transit (MRT), buses and taxi. In reference to SMRT operating data for the financial year of 2017, an average weekday ridership is 2.258 million, which is almost equivalent to half of the population are taking MRT as their daily public transport to get around. With the high amount of ridership, the reliability of the MRT is the essential factor for operation in Singapore’s transportation network. A rail failure could cost a huge maintenance cost to the operator, train delays and most importantly, comprising passengers’ safety. In the recent years, there is a significant rising of MRT breakdown. One such major disruption was due to sagging of the “third rail”, damaging the Current Collect Device. In order to prevent such incident from happening again, it is critical to detect any fault on the third rail condition so that preventive actions can be taken before disastrous situation will happen and improving the reliability of the MRT system. This report studies the real time dynamic impedance characterization of various fault condition of the in-house developed third rail jigs. The dynamic impedance characterization is collected between the CCD shoes and the third rail. The in-house third rail jigs are a scaled down version of the actual third rail from the actual MRT system. The scope of the report will cover on using LabVIEW for data acquisition for different condition of third rail jig, developing MATLAB code to calculate the dynamic impedance in terms of its magnitude and phase in time domain and analyzing the results obtained. The methodology of dynamic impedance characterization by A/P See Kye Yak, “Two port network, with inductive coupling probes” and “Time-Variant In-Circuit Impedance Monitoring” will be highly discussed and used in this project. The organization of the report will be as followed by introduction, literature review, project set up, results and finally with conclusion and future work.